Digital Twin Technology in Logistics: A Narrative Review of Implementation, Impact, and Challenges - Abdillah, Muhammad Rifqy Naufal; Wahyuilahi, Muhammad (Yayasan Sinergi Kawula Muda, 2024)
The adoption of digital twin technology in logistics has gained significant traction as organizations seek to enhance supply chain transparency, operational efficiency, and predictive accuracy. This review explores how digital twin technologies improve logistics performance, identifying what enables success and what challenges persist. Literature was collected through comprehensive searches in Scopus and Google Scholar using keyword-based Boolean strategies, with inclusion criteria focusing on peer-reviewed studies from the last decade that explicitly address digital twin applications in logistics systems. Findings reveal that digital twins enable smarter decision-making through real-time tracking and predictive tools, especially in urban and maritime logistics. Empirical evidence highlights substantial gains in logistics performance, especially in urban and maritime logistics contexts. However, systemic barriers persist, including challenges in integrating legacy systems, high implementation costs, cybersecurity risks, and shortages of skilled professionals. Comparative insights reveal a digital divide between developed and developing economies, driven by disparities in infrastructure and institutional support. To accelerate adoption, stakeholders—especially policymakers and logistics managers—must prioritize infrastructure, workforce readiness, and inclusive innovation policies. Future studies should prioritize cross-regional comparisons and develop standardized evaluation models. Overall, digital twin technology holds strong promise for transforming global logistics if supported by cohesive governance, innovation, and strategic investment.